Anatomical liver resection improves surgical outcomes for combined hepatocellular-cholangiocarcinoma: A propensity score matched study - Wang, Wen-qiang; Li, Jian; Liang, Bin-yong; Lv, Xing; Zhu, Rong-hua; Wang, Jin-lin; Huang, Zhi-yong; Yang, Shu-hong; Zhang, Er-lei (Frontiers in Oncology, 2022)
Background The efficacies of anatomical resection (AR) and non-anatomical resection (NAR) in the treatment of combined hepatocellular-cholangiocarcinoma (cHCC-CCA) remain unclear. This study aimed to compare the prognostic outcomes of AR with those of NAR for cHCC-CCA. Method Patients diagnosed with pathology-confirmed cHCC-CCA, and who underwent curative resection at Tongji hospital between January 2010 and December 2019 were included in this retrospective study. A one-to-one propensity score matching (PSM) analysis was used to compare the long-term outcomes of AR to those of NAR. Results A total of 105 patients were analyzed, of whom 48 (45.7%) and 57 (54.3%) underwent AR and NAR, respectively. There were no significant differences in short-term outcomes between the two groups, including duration of postoperative hospital stay, the incidence of perioperative complications, and incidence of 30-day mortality. However, both, the 5-year overall survival (OS) and recurrence-free survival (RFS) rates of AR were significantly better than those of NAR (40.5% vs. 22.4%, P=0.002; and 37.3% vs. 14.4%, P=0.002, respectively). Multivariate analysis showed that NAR, multiple tumors, larger-sized tumors (>5 cm), cirrhosis, lymph node metastasis, and vascular invasion were independent risk factors for poor prognoses. Stratified analysis demonstrated similar outcomes following AR versus NAR for patients with tumors > 5cm in diameter, while AR had better survival than NAR in patients with tumors ≤5 cm in diameter. After PSM, when 34 patients from each group were matched, the 5-year OS and RFS rates of AR were still better than those of NAR. Conclusion Patients with cHCC-CCA who underwent AR had better long-term surgical outcomes than those who underwent NAR, especially for those with tumors ≤5 cm in diameter. However, no differences in the risk of surgical complications were detected between the two groups.